The Use of Radiation Therapy in the Management of Selected Patients with Atypical Lipomas. (15th January 2013) - Kang, Josephine; Botros, Maikel; Goldberg, Saveli; Giraud, Christine; Nielsen, G. Petur; Chen, Yen-Lin; Raskin, Kevin; Schwab, Joseph; Yoon, Sam S.; Hornicek, Francis J.; DeLaney, Thomas F.
Abstract : Background and Objectives . Atypical lipomas are uncommon, slow-growing benign tumors. While surgery has been the primary treatment modality, we have managed some patients with radiation (RT) as a component of the treatment and have reported their outcomes in this study. Methods . A retrospective review of all cases of extremity and trunk atypical lipomas in The Sarcoma Database at the study institution was conducted. Results . Thirteen patients were identified. All patients underwent surgical resection at initial presentation and received pre- or postoperative radiation for subtotal resection (n = 2 ), local recurrence (n = 8 ), or progressive disease (n = 3 ). The median total radiation dose was 50 Gy. Median followup was 65.1 months. All patients treated with RT remained free of disease at the last followup. No grade 3 or higher late toxicity from radiation was observed. No cases of tumor dedifferentiation occurred. Conclusion . For recurrent or residual atypical lipomas, a combination of reexcision and RT can provide long-term local control with acceptable morbidity. For recurrent tumors, pre-op RT of 50 Gy appears to be an effective and well-tolerated management approach.